2019
DOI: 10.1186/s12909-019-1885-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to the role of programme directors in association with quality in postgraduate medical education – a cross-sectional study

Abstract: BackgroundEducational leaders have been pointed out as being important for quality of medical education. However, their actual influence on the education can be limited. At the postgraduate level, educational leadership and its connection with quality is underexplored and knowledge about how to increase its impact is lacking. An increased understanding could be used in order to prioritize actions for strengthening the role. The aim of this study was to investigate factors related to the role of programme direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
(27 reference statements)
0
7
0
Order By: Relevance
“…In the papers, the concept of educational leadership is used especially within medical education and within specific development cases in that field (Laksov and Tomson, 2017; Sundberg et al. , 2017; Wijk et al. , 2019).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the papers, the concept of educational leadership is used especially within medical education and within specific development cases in that field (Laksov and Tomson, 2017; Sundberg et al. , 2017; Wijk et al. , 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Context: The emphasis of the ten papers seems to be on leaders of the HE sector in the context of change. In the papers, the concept of educational leadership is used especially within medical education and within specific development cases in that field (Laksov and Tomson, 2017;Sundberg et al, 2017;Wijk et al, 2019). The Global North societies (7/10 papers) and especially, the Swedish context (4/10 papers) is accentuated in the educational leadership papers.…”
Section: The Use Of Conceptsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wijk et al reported that for a successful implementation of a programme it is necessary to form coalitions with others in addition to visions; this is particularly appropriate in the question of microbiology and clinical pharmacy, so that the interdisciplinary exchange is strengthened for all those involved in the project. Further for a successful implementation it is necessary that the educators have enough time and money to create a programme [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The articles about leadership in quality assurance work concern leaders' assessment of quality [6], their work on successfully achieving person-centered care [35], or their efforts to increase participation and inclusion [63]. Some of the articles describe problems in improvement and quality work [46,47], and some show that three factors are of specific importance in quality insurance work: teamwork, a preventive process, and a supportive organizational structure or infrastructure [14,66,68,69].…”
Section: Change Managementmentioning
confidence: 99%